2013
DOI: 10.1016/j.ijmecsci.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the behaviour of steels over large temperature and strain rate ranges

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. During forging and machining manufacturing processes, the material is subject to large strains at high strain rates which provoke local heating and microstructural changes. Modelling of these phenomena requires precise knowledge of the stress-strain constitutive equations for a large range of strains, strain rates and temperatures. An experimental study of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…a b s t r a c t A review of the different phenomenological thermo-viscoplastic constitutive models often applied to forging and machining processes is presented. Several of the most common models have been identified using a large experimental database (Hor et al, 2013). The latter consists of the tests were done in compression on cylindrical shaped specimens and in shear using hat-shaped specimens.…”
mentioning
confidence: 99%
“…a b s t r a c t A review of the different phenomenological thermo-viscoplastic constitutive models often applied to forging and machining processes is presented. Several of the most common models have been identified using a large experimental database (Hor et al, 2013). The latter consists of the tests were done in compression on cylindrical shaped specimens and in shear using hat-shaped specimens.…”
mentioning
confidence: 99%
“…5, while complementary specifications can be found in [15]. These dimensions have been selected regarding past studies [10,[13][14] and should result in a cylindrical shear band of 0.1 mm thickness (shown in Fig. 5) when compressing the hat-shaped specimen.…”
Section: Shear Tests Using Hat-shaped Specimensmentioning
confidence: 99%
“…Even if hat-shaped experiments are more representative of the cutting process, Changeux [11] noted that there are some differences considering the hydrostatic stress, the shear strain rate -even in high-speed experiments -, and mostly the dimensions of the deformed volume introducing scaling and thermal effects. Despite these differences, these tests are quite simple and were widely used for the last twenty years to characterise the behaviour of work materials, especially for metal cutting simulations [12,13]. At a macroscopic scale, Hofmann and El-Magd [14] observed that the deformation work (or strain energy) per unit volume and the shear strain at fracture obtained by hat-shaped tests can be correlated with the chip breakability of the machined material.…”
Section: Introductionmentioning
confidence: 99%
“…Pothnis et al [40] found that for both aluminium alloy 7075 T651 and IS 2062 mild steel tensile yield strength was enhanced when different strain rates were applied, if compared to quasi-static loading. Hor et al [41] conducted a number of compression and shear tests involving a wide range of temperatures (20-1000 • C) and strain rates (10 −2 -10 5 1/s). They found strong coupling of three main phenomena: effect of the temperature, effect of the strain rate and the strain hardening-softening.…”
Section: Introductionmentioning
confidence: 99%